EVALUASI PELELANGAN DAN PENGHAPUSAN ASET KENDARAAN DINAS PEMERINTAH DAERAH KOTA KUPANG (STUDI PADA BKAD KOTA KUPANG) - Logo, Emanuello Elman Peter; Bolang, Rikhard Titing Christopher; Tomasowa, Olivia Louise Eunike (Universitas Nusa Cendana, 2026)
This study aims to analyze the levels of importance and performance and to determine the position of attributes in the Cartesian Diagram of Importance–Performance Analysis (IPA) in the implementation of the auction and disposal of official vehicle assets at the Regional Financial and Asset Management Agency (BKAD) of Kupang City. This research employed a quantitative approach with a descriptive method. Data were collected through questionnaires distributed to 30 respondents and analyzed using the IPA method. The results indicate that the average importance score of 4.74 falls into the “very important” category, while the average performance score of 4.52 suggests that the implementation has generally been carried out well. However, a gap still exists between importance and performance in several attributes. The Cartesian Diagram mapping reveals that attributes A6 (completeness of asset disposal proposal documents from regional work units) and C3 (appropriateness of auction reserve prices with market conditions) are positioned in Quadrant I as top priorities for improvement. Overall, asset management has been implemented fairly well; however, improvements are still required in administrative aspects and in determining auction reserve prices to enhance effectiveness, efficiency, and compliance with public asset management principles